Enhancement of landscape elements at Taman Tasik Shah Alam, Selangor toward sustainable urban park / Ainien Sofea Mohd Zamri - Ainien Sofea, Mohd Zamri (2020)
The lack of landscape elements in terms of soft landscape and hard landscape that should be upgraded from time to time in Taman Tasik Shah Alam, Selangor. The problem of upgrading the landscape elements of the park by improving in safety, maintenance and cleanliness by achieved the goal amending Shah Alam into the City of Low Carbon 2030 or Low Carbon Cities Framework (LCCF) by providing sustainable planning and development (Saiful Adib Abdul Munaff, 2019). this research aim is to enhance the landscape elements in Taman Tasik Shah Alam, Selangor. This research-based on data collection gained from questionnaires passed at study area for Shah Alam’s locals and interview with Shah Alam’s local authority, Majlis Bandaraya Shah Alam (MBSA). The research suggested that Taman Tasik Shah Alam provided enough facilities and services to the visitors, planned for new attraction activities to fulfil the needs of Shah Alam’s community and increase the name of lake garden to protect the asset of Shah Alam, Selangor in the future. The results of the study also recommended Majlis Bandaraya Shah Alam should take care of Taman Tasik Shah Alam from time to time where it can increasing the economic and social in Shah Alam, Selangor.